Feedback inhibition of bovine herpesvirus 5 replication by dual-copy bhv5-miR-B10-3p. (14th January 2020) - Liu, Jie; Song, Xian-Rong; Zheng, Ke; Zhang, Wen-Jing; Chen, Huan-Chun; Liu, Zheng-Fei
Abstract : Bovine herpesvirus 5 (BoHV-5) is a pathogen of cattle responsible for fatal meningoencephalitis. Like alpha herpesvirus subfamily members, BoHV-5 also encodes microRNA in lytic infections of epithelial cells. BoHV-5-miR-B10 was the most abundant miRNA detected in a high-throughput sequencing study. Here, we evaluated the kinetics of miR-B10 expression after BoHV-5 productive infection by stem-loop real-time quantitative PCR. miR-B10 candidate target sites in the virus were predicted, and BoHV-5 UL39 was confirmed as a target gene by dual-luciferase assay with the design of an miR-B10 tough decoy (TuD). The UL39 gene encoding ribonucleotide reductase (RR) large subunit plays an important role in the early stage of BoHV-5 lytic infection. As BoHV-5-miR-B10 is located in internal and terminal repeat regions, we generated a TuD gene-integrated BoHV-5 strain, which effectively down-regulated miR-B10-3p. Strikingly, the suppression of miR-B10-3p significantly improved BoHV-5 replication. Taking these findings together, our study established an efficient method to deliver and express TuD RNA for viral miRNA suppression, and demonstrated that virus-encoded miRNA suppresses viral-genome biogenesis with a feedback mode, which might serve as a brake for viral replication. Herpesviruses infect humans and a variety of animals. Almost all herpesviruses can encode miRNAs, but the functions of these miRNAs remain to be elucidated. Most herpesvirus-encoded miRNA harbours dual copies, which is difficult to be deleted by current genetic modulation. Here, we developed an efficient method to deliver and express TuD RNA to efficiently suppress viral miRNA with multiple copies. Using this method, we demonstrated for the first time that viral miRNA feedback regulates viral replication by suppressing the expression of RR.